ПОРІВНЯЛЬНИЙ АНАЛІЗ МАЛОГАБАРИТНИХ ВИСОКОШВИДКІСНИХ СИНХРОННИХ МАГНІТОЕЛЕКТРИЧНИХ ДВИГУНІВ - Васьковський, Ю.М.; Нестеренко, Д.С. (Інститут електродинаміки НАН України, Київ, 2024)
Using the methods of mathematical modeling, a comparative analysis of the characteristics of three variants of small-sized high-speed synchronous magneto-electric motors (SMD) with permanent magnets on the rotor, which are intended for driving the propeller of quadcopter-type aircraft, was investigated and carried out. Namely: SMD with external grooved stator and internal rotor; SMD with internal grooved stator and external rotor; SMD with internal clear-pole stator and external rotor. On the example of an aircraft with a total mass of 4 kg, a comparative analysis of the amount of power developed by the specified engine variants under the same operating conditions: the same overall dimensions, rotor speed, current in the stator winding and volume of permanent magnets was carried out. An assessment of the magnitude of electromagnetic moment pulsations is given. It was established that although an SMD with an internal clear-pole stator is the most technologically simple, but under the same other conditions, it is inferior in power to an SMD with an internal slotted stator and an external rotor. References 7, Figures 4.